An Unusual Presentation of Takotsubo Syndrome in a Young Female of Middle Eastern Origin - Deepak Lal; Safaa AlMohdar; Mohammed Elsayed Tawfik Elsayed; Humariya Heena (Clinical Case Reports)
ABSTRACT This case of Takotsubo syndrome in a young, non‐stressed female highlight that it can present across various ages and ECG patterns, suggesting a need for further genetic research. In ECGs showing ST‐elevation myocardial infarction (STEMI), non‐invasive coronary evaluation should be prioritized over direct angiography. Echocardiographic GLS strain can help predict prognosis and facilitate early recovery.